Circular Economy Business Model for Sustainable Practices in The Smart Tourism Village - Rafdinal, Wahyu; Kusdibyo, Lusianus; Budhi Septyadi, Chandra; Dwi Wiryawan, I Gusti Ngurah (Integrasi Sains Media, 2025)
This study aims to develop a Circular Economy Business Model (CEBM) based on smart tourism for tourist villages that can be effectively applied in the context of sustainable village tourism. The study adopts a qualitative and exploratory approach, focusing on a single case study of a popular tourist village in Indonesia, recognized in the Best Tourism Village list by UNWTO. Data collection involved a combination of systematic review and interviews. The findings demonstrate that implementing a circular economy business model utilizing smart technology can enhance the competitiveness of tourist villages and drive a sustainable and smart value-creation process. Practically, this study provides insights for managers and administrators of tourist villages in implementing a smart tourism-based business model in managing tourist villages. Socially, this study contributes to raising environmental and social awareness and enhancing the welfare of the local community. This study offers new insights into the application of a smart tourism-based circular economy business model in tourist villages, an area that has been limitedly explored.